(untitled) (Research, Society and Development, 2022)
We aimed to evaluate laypeople’s visual perception of the gingival smile before and after botulinum-toxin application, using eye-tracking technology. Two frontal photographs of a female volunteer’s face with a gingival smile were used. One before and another 30 days after the toxin application in the upper lip elevator muscle region. The images were evaluated by 58 participants. Using the OGAMA software, visualization data were obtained in three areas of interest (AOI) through eye-tracking. A visual analog scale (VAS) was used to assess facial attractiveness, and a questionnaire to assess the perception of sympathy, satisfaction with the smile, dissatisfaction with dental and gingival exposure, and shyness. Heat and point maps showed that the participants visually concentrated on the mouth region, with a small transition to the nose and eyes in the pre-procedure image. The mouth region was the AOI where the first visualization occurred in a shorter time compared to the latter areas (p<0.05). VAS revealed that attractiveness increased in the image with less gingival exposure (p<0.05). After the toxin application, satisfaction with the smile increased (p<0.05), and dissatisfaction with gingival exposure decreased (p<0.05). However, dissatisfaction with dental exposure increased (p<0.05). We discovered that the mouth attracted greater attention from participants in less time compared to other AOI. The decrease in gingival exposure after the botulinum toxin application resulted in improved facial esthetics. There was a perceptible increase in “satisfaction with the smile” and a decrease in “dissatisfaction with gingival exposure.” Conversely, the “dissatisfaction with dental exposure” increased.